Predictable Roles of Peripheral IgM Memory B Cells for the Responses to Anti-PD-1 Monotherapy Against Advanced Non-Small Cell Lung Cancer - Xia, Liliang; Guo, Limin; Kang, Jin; Yang, Yi; Yao, Yaxian; Xia, Weimin; Sun, Ruiming; Zhang, Shun; Li, Wenfeng; Gao, Yuer; Chen, Hongyan; Li, Ziming; et al. (Frontiers in Immunology, 2021)
Tumor-infiltrating B cells and tertiary lymphoid structures have been identified to predict the responses to immune checkpoint inhibitors (ICIs) in cancer immunotherapy. Considering the feasibility of sample collection, whether peripheral B cell signatures are associated with the responses to ICI therapy remains unclear. Herein, we have defined peripheral B cell signatures in advanced non-small cell lung cancer (NSCLC) patients receiving anti-PD-1 monotherapy and investigated their associations with clinical efficacy. It was found that the percentages of B cells before the treatment (baseline) were significantly higher (P = 0.004) in responder (R, n = 17) than those in non-responder (NonR, n = 33) NSCLC patients in a discovery cohort. Moreover, the percentages of baseline IgM+ memory B cells were higher (P < 0.001) in R group than those in NonR group, and associated with a longer progression free survival (PFS) (P = 0.003). By logistic regression analysis peripheral baseline IgM+ memory B cells were identified as an independent prognostic factor (P = 0.002) for the prediction of the responses to anti-PD-1 monotherapy with the AUC value of 0.791, which was further validated in another anti-PD-1 monotherapy cohort (P = 0.011, n = 70) whereas no significance was observed in patients receiving anti-PD-L1 monotherapy (P = 0.135, n = 30). Therefore, our data suggest the roles of peripheral IgM+ memory B cells in predicting the responses to anti-PD-1 treatment in Chinese advanced NSCLC patients.